RECUPERAÇÃO E REAPROVEITAMENTO DA MISTURA DE CARVÃO ATIVADO EM PÓ E TERRAS DIATOMÁCEAS USADO EM PROCESSOS DE PURIFICAÇÃO DE AÇÚCARES - Olmos Yanarico, Veronica Nilza (2016)
Current policies on industrial solid waste include steps of generation, storage, transport and final disposal, thus proposing actions for minimization, reuse, recycling, treatment and disposal of these wastes. The Powder Activated Carbon (PAC) and diatomaceous earth of often used in the food industry for sugar purification. The coal residue powder activated (PA) together with the diatomaceous earth (DE), generated in the reprocessing of soft candies, it was commonly disposed in landfills. This index paper proposes the recovery of this residue by developing a regeneration method PAC-DE residue, which was proposed in two stages: the first one of cleaning with solvent (chemical treatment) and second reactivation by heat treatment (physical treatment). Given the characteristics of the compounds retained in the PAC-DE, was determined as the best solvent Ethanol 95% v/v, followed by filtration and solvent recovery by distillation. After drying to 80 °C, the washed residue passed through a heat treatment by rapid pyrolysis at 800 ° C for 15 min. With this treatment obtained a 65% regeneration of the adsorptive capacity of the mix, and 80% reduction of the gas generation process (gaseous effluents). Regenerated PAC-DE waste was applied in water treatment for oxygen chemistry demand (OCD), reduction and in the reduction of psychoactive drugs. It was obtained, for initial OCD of the 200 to 250 mgO2 L-1, a decrease for 70% by direct filtration and 60% by direct contact (Jar-Test) at a dosage of 40 mg L-1. The removal of the drug (alprazolam), for fixed bed was 100% at a concentration of 10 μg L -1. In addition, the PAC-TD regenerated it was employed in the manufacture of a new material called Green Coal Block (GCB), water resistant, with optimization prospects of the material for use in adsorption processes.